The impact of capital structure, investment growth, and liquidity on financial performance of automotive companies and its components on the Indonesia Stock Exchange (2018-2022) - Mandasari, Riska; Rikumahu, Brady (Global Academy of Business Studies, 2025)
Purpose: This study analyzes the influence of capital, investment, and liquidity structures on the financial performance of automotive companies and their components listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022. Research methodology: Multiple regression analysis was used, and data were obtained from the company's annual financial statements from 2018 to 2022. The findings of this study are expected to provide important insights for financial managers and stakeholders in managing company finances and serve as a reference for investors and creditors in evaluating the financial performance of a company. Results: The results show that capital structure has a significantly positive effect on financial performance, while investment and liquidity do not significantly affect it. Conclusion: Capital structure significantly improves the financial performance of automotive companies, whereas investment and liquidity show no significant effects. Therefore, optimizing the capital structure is crucial for strengthening financial strategies in the Indonesian automotive sector. Limitation: The study's limitation is that it focuses solely on automotive companies listed on the Indonesia Stock Exchange during the specified time frame. Contribution: The study's contribution is that it provides empirical evidence regarding the impact of capital structure, investment growth, and liquidity on financial performance in the Indonesian automotive industry, which can inform future research and practical applications in this context.